Pasting Lemmas for Some Continuous Functions: K. Kannan, K. Chandrasekhara Rao - Team, Support (Thai Journal of Mathematics, 2014)
One of the most important concepts in topological space is the pasting lemma for continuous functions. It plays an important role in algebraic topology. In the recent years pasting lemmas for some stronger and weaker forms of continuous functions such as g-continuous functions, gp-continuous functions, gpr-continuous functions, g^*b-continuous functions have been introduced by several mathematicians. In this sequel, the pasting lemmas for s^*g-continuous functions, rg^*-continuous functions and g^*r-continuous functions have been introduced in this paper.